PENGENALAN JENIS IKAN HIAS DAN SISTEM BUDIDAYA KEPADA MASYARAKAT DI NEGERI LATUHALAT KOTA AMBON - Fendjalang, Sophia N. M.; Wattimena, Martha L; Pasanea, Krisye (HIRONO : Jurnal Pengabdian Masyarakat, 2024)
Indonesia's territorial waters have an abundant and unique diversity of ornamental fish species, namely 240 types of marine ornamental fish and 226 types of freshwater ornamental fish. Negeri Latuhalat is one of the fishing villages in Ambon City where the majority of the people's livelihood comes from sea catches, namely 57% of fishing activities, which are greatly influenced by the fishing season, weather, and fuel availability which are the problems and obstacles faced by fishing fishermen. Introducing the potential and development of ornamental fish cultivation to the community is considered to be a solution for the people of Latuhalat. The activity of community service was held on Friday, July 28 2023 at 09.00 – finish at the assembly hall of Latuhalat The activity stages include preparation, implementation, and evaluation. The material was presented in 20 minutes with the topics discussed, namely the community's mindset regarding the potential of ornamental fish, freshwater and seawater ornamental fish commodities, cultivation sistems and advantages, and business opportunities for ornamental fish cultivation. Evaluation was carried out at the end of the activity by answering post-test questions and discussions according to the topic given. The conclusion from this PKM activity is that the community has increased knowledge about the potential, opportunities, and sistems for cultivating ornamental fish as well as the correct way to cultivate fish.